2010
DOI: 10.1002/chir.20916
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies on chiral rhodium complexes by ECD and VCD spectroscopy

Abstract: This article reports vibrational circular dichroism (VCD) and electronic circular dichroism (ECD) spectroscopic studies in acetonitrile on the chiral Rh(2)(O-Phe-Cbz)(1)(OAc)(3) and Rh(2)(O-Phe-Ac)(1)(OAc)(3) complexes (abbreviated Rh(2)Z(1) and Rh(2)Ac(1) , respectively; Phe, L-phenylalanine; Cbz, benzyloxycarbonyl; Ac, acetyl) supported by theoretical calculations. The ECD spectra of the complexes depend on temperature that indicates the conformational mobility of the chiral ligands. Calculations of the VCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…This is followed by a weaker negative couplet at around 1554 cm –1 , assigned to ν as (COO) of the acetate, in which the positive component band (observed at 1568 cm –1 ) contains some coupling contribution from the aromatic ring vibration. The wavenumber of the ν as (COO) band of the amino acid ligand is unusually high in comparison with the similar band at 1599 cm –1 of [Rh 2 (O‐Phe‐Cbz)(OAc) 3 ],21b which can be explained by a different binding mode of the chiral ligand. The positive band at 1444 cm –1 and the very weak negative band at 1424 cm –1 are assigned to ν s (COO) of the acetate, the latter being coupled with δ s (CH 3 ).…”
Section: Resultsmentioning
confidence: 87%
“…This is followed by a weaker negative couplet at around 1554 cm –1 , assigned to ν as (COO) of the acetate, in which the positive component band (observed at 1568 cm –1 ) contains some coupling contribution from the aromatic ring vibration. The wavenumber of the ν as (COO) band of the amino acid ligand is unusually high in comparison with the similar band at 1599 cm –1 of [Rh 2 (O‐Phe‐Cbz)(OAc) 3 ],21b which can be explained by a different binding mode of the chiral ligand. The positive band at 1444 cm –1 and the very weak negative band at 1424 cm –1 are assigned to ν s (COO) of the acetate, the latter being coupled with δ s (CH 3 ).…”
Section: Resultsmentioning
confidence: 87%
“…Recently, Szilvagyi et al [106] reported the vibrational circular dichroism (VCD) and electronic circular dichroism (ECD) spectroscopic studies for the chiral Rh 2 (O-Phe-Cbz). (OAc) 3 and Rh 2 (OPhe-Ac).…”
Section: Elucidation By Formation Of Adductsmentioning
confidence: 99%
“…20 The ECD spectra of the complexes depend on temperature that indicates the conformational mobility of the chiral ligands. The agreement between the measured and calculated VCD spectra gave unique information on the steric structure of complexes Rh 2 (OPhe-Cbz) 1 (OAc) 3 (5) or Rh 2 (O-Phe-Ac) 1 (OAc) 3 (6).…”
Section: Vcd Investigation Of Transition Metal Complexesmentioning
confidence: 99%